2021
DOI: 10.3390/cancers13246358
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Modern Radiotherapy and New Targeted Treatments for Breast Cancer Management

Abstract: Background: The objective of the present study was to review the essential knowledge about the combinations of the most commonly used or under development targeted treatments and radiation therapy (RT). Methods: Preclinical and clinical studies investigating this combination were extensively reviewed. Results: Several studies showed that the combination of RT and tamoxifen increased the risk of radiation-induced pulmonary toxicity; therefore, both modalities should not be given concomitantly. The combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 83 publications
0
10
0
1
Order By: Relevance
“…Pietras et al [ 26 ] reported that MCF-7 cells transfected with HER2 were more resistant to radiation than parental MCF-7 cells, and antiHER2-targeted therapy could reverse the radiation resistance of HER2-overexpressing cell lines by regulating the repair of radiation induced DNA damage. [ 27 ] Indeed, antiHER2 therapy can be administered under RT and has been shown to be safe, although special attention should be given with regard to cardiotoxicity. [ 28 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Pietras et al [ 26 ] reported that MCF-7 cells transfected with HER2 were more resistant to radiation than parental MCF-7 cells, and antiHER2-targeted therapy could reverse the radiation resistance of HER2-overexpressing cell lines by regulating the repair of radiation induced DNA damage. [ 27 ] Indeed, antiHER2 therapy can be administered under RT and has been shown to be safe, although special attention should be given with regard to cardiotoxicity. [ 28 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Finally, when NAC is indicated, optimizing and coordinating the timing of the different treatment modalities (i.e., systemic therapy, surgery, RT) is important [ 53 ]. Capecitabine, olaparib and abemaciclib are generally started after RT completion in order to avoid potential toxicity (concomitant use is under debate and investigation), whereas trastuzumab, pertuzumab and T-DM1 can safely be given concomitantly with RT [ 54 ].…”
Section: Post-neoadjuvant Locoregional Treatmentmentioning
confidence: 99%
“…Currently, there is no consensus guidelines for the re-testing of biomarkers after NAC, and practices vary widely [ 54 ]. The College of American Pathologists recommends that if biomarkers were negative prior to therapy, re-testing should be performed on residual invasive carcinoma after NAC.…”
Section: Pathological Evaluation Of Residual Diseasementioning
confidence: 99%
“…Even if there are some data on the association of RT and PT in other settings such as palliative bone treatment and postoperative BC treatment [ 17 , 18 , 19 ] with a favourable tolerance profile, no literature data is available on the association between PT and brain fSRT.…”
Section: Introductionmentioning
confidence: 99%